El chocolate como comida ficticia para drenaje de vías biliares - Galíndez, Lorenzo (1937)
The authors continuing their investigations about the use of fictitious meals in gall bladder drainage have found a simple and practical method. To give chocolate to patients for mastigation. The results obtained corroborate with those which prompted previous communications, and show the efficacy of the fictitious meal with an agreeable mastigating substance as chocolate. They insist in the practical importance which the procedure possess, that it is equally cheap, convenient and agreeable, and docs not demand catlieterism, which procedure besides being disagreeable may cause accidents.